La mostra (3z(BFiorentina Primaverile(3y (Bdel 1922 : Ricostruzione filologica dell'esposizione e del dibattito criticos - Emanuele Greco (Firenze University Press, 2020)
Inaugurated in Florence in 1922, the (3z(BFiorentina Primaverile(3y (Bwas an important exhibition of Italian contemporary art, conceived by the writer Sem Benelli. This exhibition remains unique to Florence because of the number (more than three hundred) and the importance of the participants (from Andreotti and Wildt, to Conti and Bacci; from macchiaioli masters like Lega and Signorini to the young artists of (S0(BValori Plastici(S1(B) as well as for the moment when it took place: a fruitful period for artistic events, like the great exhibition of the Italian Paintings from the 17th and 18th Centuries. Analyzing the archival documents of the exhibition, that have been unpublished until now, this text aims to reconstruct in a historical and critical manner, for the first time, the (3z(BFiorentina Primaverile(3y(B, in order to identify the true nature of the exhibition and, most of all, which kind of idea of Italian contemporary art was intended to be offered to the public.s
Keywords: Florence; roaring Twenties; art between World War I and World War II; Exhibition